HUBUNGAN ANTARA PENGETAHUAN MENYELAM DENGAN GANGGUAN PENDENGARAN PADA PEKERJA BAWAH AIR DI PERUSAHAAN KONSTRUKSI BAWAH LAUT - Eka Senja Koesdianasari (The Indonesian Journal of Occupational Safety and Health, 2018)
Underwater workers were prone to hearing loss. Pressure during diving and depth of dive were causing hearing loss.Jobs that are at risk for barotrauma are divers, keepers or pearl takers, marine boat keepers, rescue teams, and underwater construction work. Diving which requires a longer dive duration and deeper depth is very susceptible to health problems such as damage to the lungs, brain hemorrhage, gas poisoning and loss of body heat. This study aims to learn relationship between dive knowledge and hearing loss. The design of this research is a cross sectional study. This research is a descriptive research, because this research is the whole population. This was observational study carried out from April until June 2017 used cross sectional method. The dependent variable in this study is hearing loss, while the independent variable is diving knowledge. The result showed that obtained from 6 respondents, 100% of the respondents with bad knowledge suffer from moderate hearing loss, 60% of the respondents with sufficient knowledge suffer from mild hearing loss and 40% of the respondents with sufficient knowledge do not suffer from hearing loss. Contingency coefficient statistical test results indicate that there is a relationship between diving knowledge and hearing loss in PT Aquamarine Divindo Inspection Sidoarjo. The better knowledge can affect the respondent’s hearing loss. The conclusion in this study is the Ambang Listen Value using the audiometry test most respondents are mild deaf.Keywords: audiometric, hearing loss, underwater construction, underwater workers